Evaluation of the Healthy and Fit Prison Program (LASEGAR) in an effort to provide health services to Class IIB prisoners Sukabumi City - Kamila, Anisa; Meigawati, Dine; Amirulloh, M Rijal (International Journal of Education, Information Technology, and Others, 2024)
This study evaluates the Lapas Sehat dan Bugar (LASEGAR) program in an effort to provide health services to prisoners in Class IIB Correctional Institution of Sukabumi City. The phenomenon of the problem raised is the complexity of bureaucracy, limited resources, and the low quality of health services in prison. The purpose of this study was to assess the effectiveness of the LASEGAR program in improving health services for prisoners. The research method used is qualitative with a descriptive approach, involving observation, interviews, and document analysis. The main informants included the Head of Puskesmas Pabuaran, the Head of Class IIB Correctional Facility of Sukabumi City, and prisoners as program recipients. The results showed that the LASEGAR program successfully increased the coverage of health services, including Covid-19 vaccination (86%), NCD screening (78%), and HIV screening (30%). The evaluation also showed that the program had a positive impact in terms of reducing the spread of diseases in prisons and increasing prisoners' satisfaction with health services. However, the study also found that limited human resources and funds are still an obstacle in the implementation of the program. In conclusion, the LASEGAR program is effective in improving the quality of health services in prisons, but increased resources are needed for program sustainability.